El papel de la Conferencia de la Haya en la armonizacion del Derecho Internacional Privado - Alpízar Matamoros, Vilma (2015)
Relationships amongst people from different countries transcend frontiers without the existence of juridical regimens to regulate and resolve those type of situations. This fact gives support to the Private International Laws and international agencies like the Hague Conference in Private International Law which have assumed the task of achieving the harmonization of the private international laws in different branches such as commercial law and family law among others.